Lifetime Study of Organic Solar Cells with O-IDTBR as Non-Fullerene Acceptor - López-Vicente, R.; Fernández-Castro, M.; Abad, J.; Mazzolini, E.; Andreasen, J. W.; Espindola-Rodriguez, M.; Urbina, A. (Frontiers in Energy Research, 2021)
Organic solar cells (OSCs) have increased their power conversion efficiency (PCE) above 18% thanks to the use of non-fullerene acceptors in binary or ternary blends or in tandem configurations. In this article, a lifetime study of P3HT:O-IDTBR bulk heterojunction organic solar cells on ITO-free flexible substrates is presented. A direct comparison of glass-glass and plastic-plastic encapsulation performance, with special focus on its effect on the lifetime of the devices after degradation procedures, has been carried out complying with the ISOS protocols for organic photovoltaic devices. The manufactured OSCs with 1 cm2 active layer have power conversion efficiencies ranging from 1.9% to 3.4% depending on the encapsulant material, encapsulation process and substrate. An exponential degradation rate has been found, with a similar functional behaviour for glass and plastic differing in the degradation constants, which range from k = 0.01 h-1 to k = 0.002 h-1. Only in one case, ISOS-T3 essay for plastic encapsulation a double exponential process was observed with degradation rates of k1 = 0.03 h-1 and a second slower process with k2 = 0.001 h-1. The longest achieved T80 lifetime is 86 h for glass-encapsulated devices under an accelerated ISOS-T3 protocol.